1983
DOI: 10.1103/physrevlett.51.642
|View full text |Cite
|
Sign up to set email alerts
|

Onset of Damping in Energetic Heavy-Ion Interactions

Abstract: Measurements of longitudinal momenta transferred to mass-identified products of the fragmentation of Cu by 12 C ions give clear evidence for a change in reaction mechanism between 22 and 84 MeV/u. Results at 84 MeV/u are generally consistent with peripheral interactions. However, at 22 MeV/u large momentum transfers observed for near-target products suggest that strongly damped processes have become important. Limits to momentum transfer of the type reported by Galin et a I. are shown to arise in a natural way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1984
1984
1996
1996

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Similar results for trans-target products have been found for the interaction of copper with~~C at 15 and 22 MeV/nucleon [14,21] and 8 -28 MeV/nucleon 2oNe v~~, as described in previous publications &om our group [13 -16]. The product of this prefragment mass and v~ĩ s then P~~f or the given product.…”
Section: Fractional Velocity Transfersupporting
confidence: 83%
“…Similar results for trans-target products have been found for the interaction of copper with~~C at 15 and 22 MeV/nucleon [14,21] and 8 -28 MeV/nucleon 2oNe v~~, as described in previous publications &om our group [13 -16]. The product of this prefragment mass and v~ĩ s then P~~f or the given product.…”
Section: Fractional Velocity Transfersupporting
confidence: 83%
“…This quantity is most relevant to the central collisions. (2) The average value of the LMT for the entire distribution. This value reflects an average result integrated over all impact parameters from peripheral to central collisions.…”
Section: E Linear Momentum Transfermentioning
confidence: 99%
“…A lot of radiochemical studies have been reported for interactions of natural copper targets with lighter heavy ions over a wide ränge of projectile energies [1][2][3][4][5][6]. In particular some systematic measurements have been carried out.…”
Section: Introductionmentioning
confidence: 99%